REVISITING THE CRETACEOUS LUNGFISH ATLANTOCERATODUS IHERINGI (AMEGHINO 1898) FROM THE MATA AMARILLA FORMATION (ARGENTINA) WITH COMMENTS ON TOOTH PLATES HISTOLOGY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
Atlantoceratodus iheringi (Ameghino 1898) from Argentine territory is restudied based on its known tooth plates and newly discovered material, which includes previously unknown skull roof bones and vomerine tooth plates. The latter represent the first records of such elements from the Mesozoic era in South America. The comparative morphological analysis reveals its distinctiveness from other dipnoans, and offers valuable data for future systematic and phylogenetic research. The pterygopalatine tooth plates display narrow-based first denticulations and lack anterior wear facets, with the inner angle positioned at the level of the second denticulation. Similarly, the prearticular tooth plates feature straight mediolingual edges, and a wide-based first denticulation without sinuosities at the tip. Histological sections are performed and analyzed in detail for the first time. A. iheringi presents in this aspect distinctive features such as: large-lumen denteons tending to cluster together, circumdenteonal dentine arranged in a double band (an inner birefringent and an outer monorefringent), and a disordered interdenteonal dentine, with birefringence surrounding denteons and areas with monorefringence. A. iheringi exhibits histological structure closer to Mesozoic and Cenozoic dipnoans than Paleozoic, especially resembling the disposition observed in the Upper Cretaceous Patagonian species Metaceratodus baibianorum. The wide distribution of features designated as diagnostic for Atlantoceratodus is discussed.